2017
DOI: 10.16888/interd.2016.33.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of classroom-acoustic change on the attention level of university students

Abstract: Effects of classroom-acoustic change on the attention level of university students Interdisciplinaria, vol. 33, núm. 2, 2016, pp. 201-214 Centro Diversas investigaciones han señalado la necesidad de modificar los espacios de apren dizaje para favorecer las condiciones de salud-trabajovida de los docentes y para mejorar las condiciones de aprendizaje de los estudiantes. Dichas modificaciones implican cambios arquitectu ra les, ya sea a través de amplificadores de sonido o deflectores, que permiten variar lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
(10 reference statements)
3
18
0
2
Order By: Relevance
“…Castro‐Martínez et al 42 indicated that noise levels have an important effect on the students' attention processes, and that specific changes, aimed at decreasing reverberation values in classrooms (with at least 0.7‐0.9 seconds) affect positively the levels of attention and students' short‐term academic performance. They found that the 141 students, who participated in this study, scored significantly better ( P < 0.01) on mathematics (+59%), statistics (+18%), and attention (+14%) in a classroom with an average reverberation time of 1.2 seconds compared to students in a classroom with an average reverberation time of 2.0 seconds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Castro‐Martínez et al 42 indicated that noise levels have an important effect on the students' attention processes, and that specific changes, aimed at decreasing reverberation values in classrooms (with at least 0.7‐0.9 seconds) affect positively the levels of attention and students' short‐term academic performance. They found that the 141 students, who participated in this study, scored significantly better ( P < 0.01) on mathematics (+59%), statistics (+18%), and attention (+14%) in a classroom with an average reverberation time of 1.2 seconds compared to students in a classroom with an average reverberation time of 2.0 seconds.…”
Section: Resultsmentioning
confidence: 99%
“…Creating acceptable acoustic conditions in classrooms is important. Poor acoustic conditions can affect students' ability to hear the teacher 42 . Furthermore, Persinger et al 51 pointed out that poor acoustic conditions can cause mental health effects such as fatigue and concentration problems among students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En todo momento el sujeto se mantuvo de pie. Todo el proceso de muestreo se realizó en la sala silente para evitar que el ruido externo influyera en la grabación (Castro-Martínez et al, 2016). Las muestras de voz fueron grabadas digitalmente a una frecuencia de muestreo de 44.100 Hz y con una resolución de 16 bits.…”
Section: Procedimientounclassified
“…The acoustic environment correlates with attention levels in a classroom. Noise is an important factor of influence when identifying the words mentioned during classes and reducing reverberation values affect the levels of students' attention and performance [11]. Moreover, in order to solve noise problems, it is essential to understand and adapt the structure, organization and use of learning spaces in schools [12].…”
Section: Introductionmentioning
confidence: 99%